Efektifitas Penggunaan Model Pembelajaran Kooperatif Tipe Two Stay Two Stray Terhadap Kemampuan Pemecahan Masalah Matematika Siswa - Lynni Suryani Harahap; Puspa Riani Nasution; Andi Saputra Mandopa (JURNAL CERMATIKA, 2024)
This type of research is quasi-experimental research. The sample in this study was class VII (A and B) at Panusunan Achir Hasibuan Private MTs, totaling 40 students. This research aims to determine the effectiveness of using the Two Stay Two Stray Cooperative learning model on Mathematical Problem Solving Ability in the Spss Statistics 22 program with a significance level of 5% and n=20 which is then compared against the r table to obtain a value of 0.444. rcount > rtable, namely (0.56 > 0.444) for the pretest and (0.528 > 0.444) for the posttest. The pretest results mean the experimental class and control class were 60.95 and 61.8 respectively. For the posttest results, the average score for the experimental class was 91.90 and the control class was 79.95. The pretest and posttest normality tests for the experimental class and control class have a sig > 0.05 and the homogeneity test has a sig > 0.05, so the experimental class and control class have homogeneous data conditions. For hypothesis testing, a significant value of 0.000 <0.05 was obtained. For the N-gain Score test, the experimental class obtained an average value of 79.55% and the control class obtained an average value of 45.5%.